COOPERATIVE STRATEGIES FOR CHILDREN WITH AUTISM SPECTRUM DISORDERS IN INCLUSIVE ROBOTICS ACTIVITIES - Tsiomi, Evaggelia; Nanou, Andromachi (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
A qualitative, action research study has been conducted to investigate cooperative learning strategies for children with ASD and typical development during educational robotic activities. The participants were 4 children, 2 with ASD and 2 with typical development, around the ages of 12-14. The sessions were held at “School for all: Tokei Maru” in Thessaloniki, once a week, for 3 months. Observation protocols, researcher's diary, and interviews were used for data collection. Children with ASD, although they had a strong motivation to participate in robotic activities, exhibited disruptive behaviors. The cooperative learning strategy was not effective. Self-regulation strategies have proven helpful in limiting the disrupting behaviors of children with ASD and in supporting cooperative learning.